Pelaksanaan Layanan Administrasi Dari Whatsapp (Pandawa) Selama Masa Pandemi Covid-19 Di Kantor Bpjs Kc Depok - Ridhatul Aulia Putri; Rizma Adlia Syakurah (Politeknik Negeri Jember, 2023)
The COVID-19 pandemic has curtailed social activities in the community. The National Health Insurance implements a digital service called the Implementation of Administrative Services from Whatsapp to make it easier for JKN-KIS participants to obtain services (PANDAWA). The goal of this study is to describe the use of Whatsapp administrative services (PANDAWA) during the COVID-19 pandemic. From July 1 to 30, 2021, the Depok Branch of the National Health Insurance Office conducted this qualitative descriptive research using a case study approach. The object observed during the COVID-19 pandemic was the Implementation of Administrative Services from Whatsapp (PANDAWA) using a system approach, namely input, process, and output. The information was then analyzed descriptively. The most PANDAWA service visits were 2767 in June 2021, with a load per PANDWA officer of 1378 transactions per month; the least were 219 in August 2020, with a load per Pandawa officer of 153 transactions. PANDAWA National Health Insurance is the best innovation in providing non-face-to-face services for National Health Insurance-Indonesian Health Card (JKN-KIS) membership program participants, which are typically obtained at branch offices and can be accessed via Whatsapp. This innovation reduces visits to the BPJS Health Office, simplifies the administrative process, and can be completed from anywhere.